2018
DOI: 10.1186/s12884-018-1767-4
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an online intervention in preventing excessive gestational weight gain: the e-moms roc randomized controlled trial

Abstract: BackgroundExcessive gestational weight gain (GWG) is common and contributes to the development of obesity in women and their offspring. Electronic or e-health interventions have the potential to reach large groups of women and prevent excessive GWG, but their effectiveness has not been demonstrated. The purpose of this study was to evaluate, in a real-world setting, the effectiveness of a self-directed, integrated online and mobile phone behavioral intervention in preventing excessive GWG.MethodsThis effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(106 citation statements)
references
References 34 publications
1
102
2
1
Order By: Relevance
“…However, the usage level slumped after the initial excitement to a rather moderate level, which was more evident among inactive users. While the engagement level of the current study was better than the e-moms roc trial reported by Olson et al, it remained shy of anticipated as indicated by the nonsigni cant improvement in diet or physical activity (14).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, the usage level slumped after the initial excitement to a rather moderate level, which was more evident among inactive users. While the engagement level of the current study was better than the e-moms roc trial reported by Olson et al, it remained shy of anticipated as indicated by the nonsigni cant improvement in diet or physical activity (14).…”
Section: Discussioncontrasting
confidence: 74%
“…eHealth solutions provide a promising tool to enable such intervention in a more resource and user friendly manner. So far, limited examples, including the unsuccessful e-moms roc trial, and partially successful SmartMoms intervention, call for more endeavors to identify approach that can consistently deliver positive results (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…All studies were published between 2012 and 2019. Of the 11 studies, 7 were randomized pilot or feasibility studies [ 31 - 37 ] and 4 were RCTs [ 38 - 41 ]. Of the 4 RCTs, 2 reported being adequately powered [ 39 , 41 ], whereas the other 2 reported being underpowered as a result of a small starting sample [ 40 ] or low follow-up rate [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Herring et al [ 117 ] and Willcox et al [ 118 ] provided regular health coaching regarding lifestyle, physical activity, and GWG to women via Facebook, text-messaging and/or a website, booklets, and phone-calls. Olsen et al [ 119 ] and Smith et al [ 120 ] based their interventions on websites and Jackson et al [ 121 ] described an intervention that added ‘Video Doctor’ counseling in addition to their routine antenatal care ( Table S3 ). Three eHealth interventions [ 117 , 118 , 120 ] were included in a meta-analysis which favored neither intervention nor control (WMD: −1.06; 95% CI: −4.13, 2.00, p = 0.50; I 2 = 73.6%) ( Table 1 ) ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%